STRATEGI PENGELOLAAN KAWASAN PERMUKIMAN PESISIR KOTA SELATPANJANG - Risqiana Dani; Zulfan Saam; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2013)
Coastal settlement region with all the uniqueness of nature, beauty and appeal is an idealarea for development of settlement activity. The fact that the population growth rate is highwill result in changes to the existing ecosystem. Environmental conditions of coastal Selat panjang city not arranged properly, moreover high level of poverty is one of reason thedecent settlement have not been fulfilled. The purpose of this study is to identify thecharacteristics of the coastal settlement Selatpanjang city, analyzed the usefulness of physicalsettlement as a living space, to support social, cultural and economic activities and todetermine the management strategies of coastal settlement Selatpanjang city. This study isusing the method of survey research and to transform quantitative data into qualitative datause a Likert scale. The result of this study found that the characteristics of the coastalsettlements of Selatpanjang city is dominated by the use of land up the majority of populationis used as a settlement, settlement condition is largely a non-permanent settlements and semi-permanent, and not the presence of coastal buildings yet. Physical conditions compatibilitylevel of the settlement as a living space with a residential component of legality, buildingstructure, the living space per occupant, water supply, availability of bathroom facilities,trash heap services and the electricity grid was found that the condition of occupancy “LessUnder” as a living space, the next level of concordance as a means of supporting social,cultural and economic activities of coastal communities Selatpanjang city with assessmentcomponent of health, education, religious duties, government and public services, open area,trade and services obtained results “Less Under”, so it is necessary to repair or provision ofthe settlement. Strategic management of the coastal settlement Selatpanjang city to do withthe control of land use, increased as a function of residential living space, improving thequality of neighborhoods as well as the improvement of housing facilities and infrastructure.